‘Seeking Justice, Not Charity’. Medical Experiment Victims’ Struggle with Purposefully Inadequate Compensation - Weinberger Ruth Jolanda (Eastern European Holocaust Studies)
Germany’s initial Wiedergutmachung process did little good for survivors of Nazi medical experiments who struggled with uniquely devastating circumstances. Unable to navigate the nascent post-war compensation bureaucracy, many were left with shockingly little financial assistance, or none at all. That was even the case for one of the victims, Haim Nahon, who had the leadership of the primary restitution agency personally fighting on his behalf. Despite the focus of the Conference on Jewish Material Claims Against Germany on communal relief and rehabilitation and not on individual compensation, Nahon’s plight was taken up by Benjamin Ferencz, Saul Kagan and other senior figures involved in Wiedergutmachung. Yet even their direct involvement in early compensation efforts, documented in this article in granular first-person accounts, could do little to help Nahon’s case. Nahon’s failed attempts to obtain “adequate” post-war compensation from Germany’s Ministry of Finance offer an unsettling case study of how willfully limited interpretations of the initial 1951 restitution fund had a lifelong cost for survivors of Nazi medical experiments.